Respuesta :

consecutive integers are 1 apart
they are x,x+1,x+2

their sum is -3
x+x+1+x+2=-3
3x+3=-3
minus 3 both sides
3x=-6
divide both sides by 3
x=-2
x+1=-1
x+2=0

product of their cubes is (-2)³(-1)³(0)³=0, wot, how do we get to 49


let's start over

lets start with 'the sum of their cubes is 49 and ignore the sum of the terms is -3

so

(x)³(x+1)³(x+2)³=49
expand
(x³)(x³+3x²+3x+1)(x³+6x²+12x+8)=49
x⁷+9x⁶+33x⁵+63x⁴66x³+36x²+8x=49
x⁷+9x⁶+33x⁵+63x⁴66x³+36x²+8x-49=0
solve  by graphing
x≈0.627194
x+1≈1.67194
x+2≈2.67194

dunnow about their sum being -3 but it definitatel ain't equal to -3